Contextual Mind Mapping Facilitates Reading Comprehension For Deaf Elementary Students: Pemetaan Pikiran Kontekstual Memfasilitasi Pemahaman Membaca Bagi Siswa Tunarungu Sekolah Dasar - Mersita Mersita; Rendy Roos Handoyo (Academia Open, 2026)
General Background Literacy acquisition constitutes an essential foundation for academic success across all educational subjects. Specific Background Fifth-grade learners with hearing impairments frequently struggle to understand narrative texts due to conventional instruction and an absence of visual learning media. Knowledge Gap Although visual graphic organizers and real-life pedagogical approaches have been extensively studied separately, their combined application to accommodate marginalized learners in inclusive classrooms remains severely underexplored. Aims This Classroom Action Research evaluates the implementation of Contextual Teaching and Learning (CTL)-based visual media to support the narrative text processing of a hearing-impaired fifth-grader alongside their peers. Results Following two instructional cycles, the focal participant's academic score progressed from a 45 baseline to 60 in Cycle I, ultimately achieving 80 in Cycle II, thereby surpassing the minimum mastery criterion. Concurrently, learner engagement escalated as individuals actively constructed visual nodes, identified main ideas, and connected written content to real-life experiences. Novelty This study uniquely integrates a visual graphic organizer with contextual learning principles specifically tailored to address the cognitive and communication characteristics of special educational needs learners within an inclusive setting. Implications Educators must adopt visually rich, contextualized instructional strategies to reduce cognitive load and facilitate meaningful literacy acquisition for individuals facing auditory constraints. Highlights The integration of a visual graphic organizer with real-life connections significantly elevated learner engagement during narrative text lessons. The focal participant's academic score progressed from a failing 45 to an 80, surpassing the minimum mastery threshold. Reducing textual information into structured visual nodes minimized cognitive load for individuals with special educational needs. Keywords Reading Comprehension; Hearing Impairment; Mind Mapping; Contextual Teaching; Inclusive Education